A Study on RFID Technology Combined Lean Implementation in Malaysian Automotive Industry - Zeeshan Rafique, Muhammad; Nizam Ab Rahman, Mohd; Saibani, Nizaroyani; Arsad, Norhana (International Journal of Engineering and Technology, 2019)
RFID technology is one of the prominent and progressive technology from the previous years. Currently the RFID technology has utilized in different prisms and works like a catalyst in case of Lean Manufacturing as it certainly speeds up the manufacturing processes through providing them operational visibility. Based on this idea, the authors of this research study has conducted a case study which results in a real time based pilot study that has been done to explain the implementation of RFID technology in combination of lean manufacturing in plant operations forÂ application in real world. This research is not only beneficial for engineering managers but also for academicians as it includes ROI to confirm the usefulness and viability of research and also enlightens the way to how to achieve improvements.Â Â